Analisis Penerapan Tatakelola Pemerintahan dalam Pengelolaan Dana Desa di Desa Pentadu Barat Kecamatan Tilamuta - Sukrianto (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to examine how governance is implemented in the management of Village Funds in Pentadu Barat Village, Tilamuta District, Boalemo Regency. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document study. Data analysis follows the Miles and Huberman model, which consists of three stages: data reduction, data display, and conclusion drawing/verification. The results of the study indicate that: (1) The implementation of governance in managing Village Funds—which includes participatory planning, transparent implementation, and accountable reporting—has met the standards of Village Fund management and reflects the principles of good governance; (2) Community perceptions of the Village Fund allocation for development and empowerment programs show a noticeable improvement in infrastructure and community well-being. However, this study has several limitations, including its narrow focus on a single village, the subjectivity inherent in a qualitative approach, and the relatively short duration of observation. Therefore, future researchers are encouraged to expand the study area, adopt a mixed-methods approach, and conduct longer-term observations to obtain more comprehensive and representative findings.